Ca9La(PO4)7:Eu2+,Mn2+: a radiation-adjustable phosphor usable for high-perfomance white light-emitting diodes - Phuc Dang Huu; Phung Ton That; Phan Xuan Le; Nguyen Le Thai (Institute of Advanced Engineering and Science, 2022)
We used solid-condition processes to make a sequence of radiation-adjustable phosphors Eu2+/Mn2+ co-doped Ca9La(PO4)7 (shortened as CaLa:EM), which show a consistently variable hue from green to yellow and red via an efficient resonance-form energy transition as well as the strength of green and red radiations may be controllable through altering the Mn2+concentration. We examined the transition of energy (Eu2+®Mn2+) for CaLa:EM. It is proved to be a resonant kind using a dipole-quadrupole process, having power shift critical range calculated to be 11.36 Å by using the spectral overlap techniques. Mixing a 365 nm UV-InGaN chip as well as one phosphor combination containing (Ca0.98Eu0.005Mn0.015)9La(PO4)7 in yellow with BaMgAl10O17:Eu2+in blue produced a warming WLED having CIE color coordinates measured at (0.35, 0.31), better CRI value (Ra)measured at 91.5 along with smaller CCT value of 4,496 K.